Коммуникативные процессы в виртуальном гиперпространстве - Рекун, Иван (Wydawnictwo Uniwersytetu Rzeszowskiego, 2008)
The functional possibilities of the computer technologies create not only a new kind of mass communication but also a new sphere of social co-operation. It determines substantial modification of a modern person’s mentality and modernization of social structures providing system change of the human activity’s nature and lifestyle of every member of information society.

Funkcjonalne możliwości technologii komputerowych kształtują nie tylko nowy rodzaj komunikacji masowej, ale również nową sferę społecznej współpracy. Określa to istotną modyfikację mentalności współczesnej osoby i modernizację struktur społecznych, powodując systemową zmianę natury ludzkiej aktywności i stylu życia każdego członka społeczeństwa informacyjnego.
Communicative Processes in the Virtual Hyperspace
Procesy komunikacyjne w wirtualnej cyberprzestrzeni